Chapter Modeling Forest Floor Biomass and N Accumulations and Related Turnover Rates - Arp, Paul A. (Taylor & Francis, 2024)
The second edition of Ecological Forest Management Handbook continues to provide forestry professionals and students with basic principles of ecological forest management and their applications at regional and site-specific levels. Thoroughly updated and revised, the handbook addresses numerous topics and explains that ecological forest management is a complex process that requires broad ecological knowledge. It discusses how to develop adaptive management scenarios to harvest resources in a sustainable way and provide ecosystem services and social functions. It includes new studies on ecological indicators, the carbon cycle, and ecosystem simulation models for various forest types: boreal, temperate, and tropical forests. NEW IN THE SECOND EDITION Provides a comprehensive collection of sustainable forest management principles and their applications Covers new ecological indicators that can be applied to address forest environmental issues Includes all types of models: empirical, gap, and process-based models Explains several basic ecological and management concepts in a clear, easy-to- understand manner This handbook is intended for researchers, academics, professionals, and undergraduate and graduate students studying and/or involved in the management of forest ecosystems. Chapter 18 of this book is available for free in PDF format as Open Access from the individual product page at www.taylorfrancis.com. It has been made available under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 license.